The Concept of Ethics in the Intensive Care - Kutay Alpir (Galenos Yayinevi, 2010)
The concept of ethics in the intensive care unit has developed in the last 50 years along with the advancements and regulations in this area of medicine. Especially by the use of life-supportive equipment in the intensive care units and the resulting elongation in the terminal stage of life has led to newly described clinical conditions. These conditions include vegetative state, brain death, dissociated heart death. The current trend aiming to provide the best health care facilities with optimal costs resulted with regulations. The conflicts in the patient-physician relations resulting from these regulations has resolved to some extent by the studies of intensive care unit ethics. The major ethical topics in the intensive care are the usage of autonomy right, the selection of patients to be admitted to the intensive care unit and the limitation of the treatment. The patient selection is optimized by triage and allocation, the limitation of the treatment is done by the means of withdrawal and withhold, and the usage of autonomy right is tried to be solved by proxy, living will and ethics committee regulations. The ethical regulations have found partial solutions to the conflicts. For the ultimate solution much work about the subject has to be done. (Journal of the Turkish Society of Intensive Care 2010; 8: 77-84)